A STUDY ON THE IMPACT OF GLOBAL WARMING ON WILDLIFE - Varis, Md. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Global warming, a pressing issue of our time, is exerting a profound influence on the delicate balance of our planet's ecosystems. Among its far-reaching consequences, the impact on wildlife is particularly alarming. As temperatures rise, sea levels climb, and weather patterns become increasingly erratic, countless species are facing unprecedented challenges to their survival. One of the most significant impacts of global warming on wildlife is habitat loss. As temperatures rise, ecosystems are shifting, and many species are struggling to adapt to these changes. For example, the melting of polar ice caps is threatening the existence of polar bears, seals, and other Arctic species. Similarly, coral reefs, which are vital habitats for countless marine organisms, are bleaching and dying due to rising ocean temperatures and acidification. Climate change is also disrupting the delicate timing of biological events, such as migration and breeding. Many species rely on specific environmental cues, such as temperature and day length, to trigger these behaviors. However, as these cues shift due to climate change, animals may miss critical opportunities for feeding, breeding, or migrating, leading to population declines.